A NEW PROOF OF CLARKE'S THEOREM - Gue Myung Lee; Phạm Tiến Sơn (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, we give a new proof of the theorem of Clarke on Fritz John optimality conditions for nonsmooth optimisation problems involving locally Lipschitz functions.